Evolving patterns of lower limb amputations at a Nigerian tertiary hospital: a retrospective study - Hart, Fiekabo; Orupabo, Furo (International Surgery Journal, 2025)
Background: This study aims to review the current trends in the demographics of lower limb amputation at the University of Port Harcourt Teaching Hospital, Nigeria. Methods: This is a retrospective, hospital-based chart review of all patients who underwent lower limb amputation at the University of Port Harcourt Teaching Hospital (UPTH) between January 1, 2020 and December 31, 2024. Results: A total of 111 lower limb amputations were performed within the period under review. 74 males and 37 females giving a male: female ratio of 2:1. Mean age 45.3±20.5, peak age of amputation 61-69 years with 24 patients (21.6%), diabetic foot disease was the highest indication for amputation (36.9%), majority had above knee amputation (50.5%), with 95.1% discharge. Conclusions: The major concern is the prevention of amputation. As reported in this study, diabetic foot disease is the main indication for amputation. Education on diabetic foot care will reduce this incidence. Government involvement in improving the poor economic situation will further improve access to health facilities and drugs for management of diabetes mellitus.